Różnice we wdrażaniu zasad promocji zdrowia w szkołach w czasie pandemii COVID-19. Rozważania oparte na badaniach przeprowadzonych wśród dyrektorów polskich szkół - Leksy, Karina (Studia Edukacyjne, 2023)
During the coronavirus pandemic, health promotion became crucial for preventing COVID-19 disease and mitigating its consequences. Implementing health promotion principles was particularly essential in educational settings, where the possibility of infection was high. Simultaneously, only limited empirical studies have addressed school principals’ perspectives on implementing health promotion issues during the COVID-19 pandemic. Thus, this study aims to examine the differences in implementing health promotion principles in schools during the COVID-19 pandemic. The results come from an online cross-sectional survey conducted in eight provinces of Poland from June to December 2021. The study was part of a global school principal health literacy survey under the COVID-HL Network. Research results have shown that schools in the Health Promoting Schools network tend to implement the whole-school approach to health more often. In addition, the longer the school belongs to the network, the more health promotion activities are implemented. It can be assumed that school principals play a crucial role in implementing health promotion principles in schools. Therefore, their health awareness and interest in health matters are essential for effectively promoting health in schools.